Review of the Fund's Strategy on Overdue Financial Obligations. (Policy Papers; Policy Paper ;, 2006)
This paper reviews progress under the Fund's strengthened cooperative strategy on overdue financial obligations since the last review and proposes to extend the availability of the rights approach by another year, to end-August 2007. Section II reviews recent developments regarding overdue financial obligations to the Fund through end-June 2006. Progress under the Fund's strategy on arrears and developments in the protracted arrears cases are discussed in Section III. A draft decision to extend the availability of the rights approach until end-August 2007 is provided in Section IV.